KONSEP FITRAH DAN PENGEMBANGANNYA DALAM PENDIDIKAN ISLAM DI ERA DISRUPSI DIGITAL (PERSPEKTIF AL-QUR’AN DAN HADIS) - Wastuti Wastuti; Mahyuddin Barni; Abd. Majid Abd. Majid; Iskandar Iskandar (EDUPEDIA, 2025)
This study aims to analyze the concept of fitrah from the perspective of the Qur’an and Hadith and to examine its relevance for the development of Islamic education in the digital disruption era. The research employs a library research method, using primary sources such as Qur’anic verses, Prophetic traditions, and classical literature on fitrah, as well as secondary sources derived from contemporary studies on Islamic education and the challenges of the digital age. The analysis was conducted through thematic content analysis, encompassing etymological, conceptual, and pedagogical dimensions. The findings indicate that fitrah represents the fundamental theological potential of human beings—encompassing an innate inclination toward monotheism, truth, and morality—which may either develop or deviate depending on environmental influences. The Qur’anic perspective (Qur’an Ar-Rum:30; Al-A’raf:172) and Prophetic traditions (Bukhari and Muslim) affirm that all humans are born in a state of purity and are naturally predisposed to receive divine values. In the educational context, the digital disruption era presents challenges such as the rapid flow of information, moral relativism, digital hedonism, and the shifting of educational authority. The results further emphasize that the development of fitrah must be carried out integrally through the strengthening of faith, the habituation of noble character, value-based digital literacy, educator role-modeling, and the creation of an Islamic educational environment. Thus, Islamic education holds a strategic role in preserving the purity of fitrah and shaping learners with a strong Islamic identity, moral resilience, and the capacity to adapt to technological change.